Methane reductions with gypsum and SOP® lagoon additives in liquid manure - Chelsea Sauvé; Chelsea Sauvé; Hambaliou Baldé; Rajinikanth Rajagopal; Andrew VanderZaag (Frontiers in Climate)
The agriculture industry is an important source of greenhouse gas emissions globally with livestock production being a main contributor. Therefore, there is a need to reduce methane (CH4) emissions from livestock production, including liquid manure storages. Using an additive that decreases methanogenesis is one approach currently being considered. This study tests two additives: SOP® Lagoon (a commercial additive) and a commonly used, local fertilizer, gypsum. The objective was to determine the capability of the two products to reduce CH4 emissions. Tests were done at 24°C in the laboratory with multiple rates of the additives (100, 1,000, 5,000 and 10,000 g/m3). Methane produced by untreated dairy manure (control) was compared to manure with addition of gypsum or SOP® Lagoon over 162 days. Results showed that peak CH4 reduction occurred between 20 and 30 days, then declined. The lowest dose of both additives (100 g/m3) did not significantly reduce CH4 over the duration of the study. Efficacy increased non-linearly with an increasing dose up to 5,000 g/m3. After 30 days, CH4 reduction decreased by 32, 73, 74% for SOP® Lagoon rates 1,000, 5,000, 10,000 g/m3, and 20, 60, and 63% for gypsum. Both SOP® Lagoon and local gypsum showed similar reduction in methane emissions at similar application rates. This is an indication that farmers can confidently use locally sourced gypsum, a low-cost alternative to the commercial additive, without affecting the overall mitigation potential.